Study on the Precursor Characteristics of Instability Failure of Gas-Bearing Coal Based on Stress and Gas Seepage Volume. (25th July 2022) - Xie, Hui; Ma, Yankun; Liu, Xiaofei; Li, Jinduo; Gao, Ang; Du, Zinan
Abstract : In coal mining activities, the original stress of the coal body changes, resulting in structural deformation and destruction, which will cause changes in gas seepage volume. The conventional triaxial loading test was carried out by using the triaxial loading-gas adsorption seepage experimental device. The effects of different loading rates, confining pressures, and gas pressures on the peak strength of coal were analyzed; the evolution laws of coal stress, gas seepage volume, stress rate, and gas seepage volume rate at different deformation stages were studied; and it was found that the time, at which the specimen began to enter the crack propagation deformation stage, determined by the change of gas seepage rate or stress rate was not the same. Therefore, combined with gas seepage and stress, a theoretical model of stress rate-seepage volume rate under triaxial pressure was proposed, and the ratio F of the two was used as an early warning index. It was found that the F value was basically stable in the elastic stage and decreased rapidly in the crack propagation stage. Thus, the F value was used as an early warning index for the instability and failure of gas-bearing coal. The F value of the experimental results was consistent with the theoretical model, and the F value entered the crack propagation stage earlier than the stress rate or the gas seepage volume rate. The research results provided a theoretical basis for coal mine safety mining and disaster prevention.